2014
DOI: 10.1016/j.abb.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific insertion of selenium into the redox-active disulfide of the flavoprotein augmenter of liver regeneration

Abstract: Augmenter of liver regeneration (sfALR) is a small disulfide-bridged homodimeric flavoprotein with sulfhydryl oxidase activity. Here, we investigate the catalytic and spectroscopic consequences of selectively replacing C145 by a selenocysteine to complement earlier studies in which random substitution of ~90% of the 6 cysteine residues per sfALR monomer was achieved growing Escherichia coli on selenite. A selenocysteine insertion sequence (SECIS) element was installed within the gene for human sfALR. SecALR2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Meanwhile the Bf-flavin is not mobile relative to residue 37 and is 12 Å away from the nearest aromatic side chain based on our model and available structures (14). Cys is competent to form a CT complex with OX Bf-flavin, especially upon ionization (76,77). However C174.L was proven not to be required for 726 nm species formation by our C174A.L variant.…”
Section: Discussionmentioning
confidence: 71%
“…Meanwhile the Bf-flavin is not mobile relative to residue 37 and is 12 Å away from the nearest aromatic side chain based on our model and available structures (14). Cys is competent to form a CT complex with OX Bf-flavin, especially upon ionization (76,77). However C174.L was proven not to be required for 726 nm species formation by our C174A.L variant.…”
Section: Discussionmentioning
confidence: 71%
“…Epidemiological studies have suggested the correlation of Se deficiency and poor prognosis of the spinal cord [ 46 ] and liver regeneration [ 47 ]. However, there is still no direct evidence that selenium benefits tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the nature and consequences of this substitution were the main goals of many recent biochemical and theoretical studies. 22,23 Herein, the syntheses and crystal structures of Co(III) complexes with thiosemicarbazone and selenosemicarbazone ligands are reported. To obtain detailed characterization of these compounds, which could provide a better insight into the structure-activity relationship, cyclic voltammetry, NMR and UV/Vis spectroscopic analyses and the measurement of antioxidant capacity are presented together with a theoretical study.…”
Section: Introductionmentioning
confidence: 99%